MUSHAF UTHMANI: KAJIAN SEJARAH DAN PERKEMBANGANNYA DALAM MENJAGA KEOTENTIKAN AL-QUR’AN - Abdul Wahid (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2022)
Mushaf Uthmani is a mushaf had related to khalifah Uthman bin Affan and al-Quran had copied from early original writen in Nabi muhammad SAW. era in Hafsah’s house. The mushaf had experience development from compile, giving wowel ect. This research is to understand historical process and development of al-Quran Mushaf Uthmani. The method used is book literature. In early Mushaf uthmani’s writen doesn’t have wowel and make it us Arab difficulty in reading. Because of that, al-Quran’s writen had completed since in umayyah era to easier read it. Eventhough al-Quran had development but the originality had protected from fabrication.